Using Newton's method to model the spatial light distribution of an led with attached secondary optics - Kaljun, David (Strojniški vestnik, 2016)
In the design of optical systems based on light emitting diode (LED) technology, a crucial task is to handle the unstructured data describing the properties of optical elements in standard formats. This leads to the problem of data fitting within an appropriate model. Newton's method is used as an upgrade of the previously developed most promising discrete optimization heuristics showing an improvement in both performance and the quality of solutions. This experiment also indicates that a combination of an algorithm that finds promising initial solutions as a preprocessor and Newton's method may be a winning idea, at least on some datasets of instances
Keywords: diskretna optimizacija; LED; light-emitting diode; lokalno iskanje; metoda najmanjših kvadratov; Newtonova metoda; porazdelitev svetlobe